Bidirectional Influence between Language and Cognitive Functions: Exploring how Language Affects Thinking and Vice Versa - Espinel Jaramillo, Andrés (Revista Ecos de la Academia, 2024)
This article was aimed to analyze the bidirectional influence between language and cognitive functions, investigating how language affects thinking and vice versa. To this effect, a mixed and critical approach methodology was used, which facilitated an interview and survey with a psychologist and 37 teachers from the Jason Miller School. This, to find out about their experience in the classroom and institution in relation to the subject. The results indicated that the majority of respondents, 81%, believe that language has a significant impact on students’ cognitive functions. This perception is supported by scientific evidence, which suggests that language is not only a communication tool, but also a key factor in cognitive development and the way information is processed. Among the findings, 59.5% of teachers noted differences in the academic performance of students with language difficulties, highlighting the bidirectional influence between language and cognitive functions. Finally, individual tutoring was the most used measure (54.1%) to support students with language difficulties in the teaching-learning process.